2010
DOI: 10.5551/jat.1578
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ezetimibe on Surrogate Markers of Cholesterol Absorption and Synthesis in Japanese Patients with Dyslipidemia

Abstract: Aim:To demonstrate the clinical benefit of inhibiting intestinal cholesterol absorption, we evaluated the effects of ezetimibe on surrogate markers of cholesterol absorption and synthesis, lipid and glucose metabolism, and markers of obesity and inflammation. Methods: A total of 120 patients with dyslipidemia (46 men; mean age 66.5 years), who had not achieved the low density lipoprotein cholesterol (LDL-C) goal recommended by the Japan Atherosclerosis Society Guideline despite diet and exercise or any statin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 22 publications
9
39
0
1
Order By: Relevance
“…These results suggested that glucose tolerance was not exacerbated by ezetimibe. Several studies in humans 16,17,26) showed that HbA1c was decreased by ezetimibe. The results of our animal study 25) supported the concept that ezetimibe ameliorates hepatic insulin resistance as well as dyslipidaemia and hepatic steatosis in high-fat dietinduced obese subjects.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that glucose tolerance was not exacerbated by ezetimibe. Several studies in humans 16,17,26) showed that HbA1c was decreased by ezetimibe. The results of our animal study 25) supported the concept that ezetimibe ameliorates hepatic insulin resistance as well as dyslipidaemia and hepatic steatosis in high-fat dietinduced obese subjects.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Clinically, the administration of ezetimibe has been shown to reduce fasting levels of total cholesterol (TC) and LDL-C in patients with primary hypercholesterolemia in both Japan and the United States 13,14) . In addition, ezetimibe has been reported to reduce postprandial hypertriglyceridaemia and inflammation and to improve insulin sensitivity 15,16) . In animals experiments, ezetimibe reversed dietinduced obesity 17,18) , liver steatosis [17][18][19][20] , and insulin resistance 19) .…”
Section: Measurement Of Serum Samplesmentioning
confidence: 99%
“…1 However, studies have also demonstrated an action of ezetimibe in the reduction of blood insulin and HbA1C levels. 2 Possible mechanisms include an increase in glucagon-like peptide-1 activity and in pancreatic beta cell mass, which have been observed in animal models. 3 This is consistent with the finding of increased insulin sensitivity in NPC1L1 knock out mice, or in mice treated with ezetimibe, when exposed to a diabetogenic diet.…”
Section: To the Editormentioning
confidence: 99%
“…This finding validates the concept that lifelong LDL cholesterol reduction has a greater impact on risk 1 than pharmacologic interventions, such as statin therapy, initiated later in life. 2 We have previously hypothesized that increased dietary sterol (cholesterol and xenosterol) absorption via NPC1L1 is associated with increased cardiovascular risk. 3,4 We further posit that there are sterol species in our diets (such as oxysterols, oxyphytosterols, etc.)…”
Section: Doi: 101056/nejmc1500124mentioning
confidence: 99%
“…48,49 Ezetimibe monotherapy has also been observed to be associated with an improvement in visceral fat area, fasting insulin level, homeostasis model assessment of insulin resistance and hs-cRP level in patients with fatty liver. 50 hs-cRP is an important inflammatory biomarker related to adverse cardiovascular outcomes, 51,52 and studies have consistently shown a significant reduction in hs-cRP levels with ezetimibe-statin combination therapy.…”
mentioning
confidence: 99%